2017
DOI: 10.5507/bp.2017.054
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-hospital cardiac arrest

Abstract: aOut-of-hospital cardiac arrest (OHCA) is a leading cause of death in developed industrial countries. The global worldwide average of OHCA incidence in adults is 95.9/100,000/year. European incidences vary according to source from 16 to 119/100,000/year. The aim of this study was to provide an overview of current information on OHCA. The incidences in various populations are discussed, along with the factors affecting the prognosis and outcome of these patients. The etiology and pathophysiological mechanisms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
46
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 23 publications
1
46
0
4
Order By: Relevance
“…Sudden cardiac death remains one of the leading causes of death in developed countries[1] and is considered as a major burden to the population[23]. In the early 21 st century, there were approximately 600–700 non-traumatic out-of-hospital cardiac arrest (OHCA) cases annually in the Daegu Metropolitan City area; this number increased from 887 in 2012 to 1009 in 2016[4].…”
Section: Introductionmentioning
confidence: 99%
“…Sudden cardiac death remains one of the leading causes of death in developed countries[1] and is considered as a major burden to the population[23]. In the early 21 st century, there were approximately 600–700 non-traumatic out-of-hospital cardiac arrest (OHCA) cases annually in the Daegu Metropolitan City area; this number increased from 887 in 2012 to 1009 in 2016[4].…”
Section: Introductionmentioning
confidence: 99%
“…SCD is an unexpected death occurring generally within 1 h of onset of symptoms [ 3 ]. The most common cardiovascular diseases that lead to SCD are coronary atherosclerosis and dilated cardiomyopathy, where the loss of cardiac mechanical function and decreased cardiac output can result in the genesis of malignant ventricular arrhythmias [ 3 ]. Koldobskiy et al have found that renal disease, immunosuppression and obesity are associated with lower success rate to cardiopulmonary resuscitation [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The global incidence of cardiac arrest with assumed primary cardiac cause is 55/100 000 inhabitants. 1 In Europe, approximately 275 000 people with all-rhythm cardiac arrests are treated by the emergency medical systems (EMS) each year. 2 Out-of-hospital cardiac arrest (OHCA) is a significant cause of global mortality.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, in recent years the survival rates have improved especially in developing countries due to advances in the chain of survival. 1 At present, the majority of published OHCA studies focus on the acute prehospital and intensive care treatment of OHCA sufferers. Far fewer studies have investigated the period from early recovery to long-term return to everyday life.…”
Section: Introductionmentioning
confidence: 99%